Modeling the Learning Disabilities in Student Population - R, Jamuna (International Journal of Computer Sciences and Engineering, 2019)
The paper analyzes many learning disabilities prevalent in male and female sample student population which describes how the significance of the problems can be used to pinpoint the existence of educational problems related to health. A learning problem or disability can be seen as spanning a continuum from mild to severe. We will use the term “learning disability” to define the milder educational problems. The severity of the learning problem depends on the number and severity of processes affected. Statistics show that a large number of students are academically inhibited that they have trouble in holding their professional status also in later years. Many students all over the world suffer from some form of learning disability like arithmetic difficulties, verbal disability, memory retention disorders etc. Personal characteristics like introvert nature, inferiority complex, attention deficiency etc reduce their academic progresss. The social factors trigger these problems that they do not fit into their peer groups. They also exhibit learning disabilities due to biological factors like parents to sibling disorders, chromosomal disorders etc. It can also be due to psychological factors like lack of self confidence, lack of motivation, not adaptability etc. To model this problem we use Chi-square variate to find the independence of two attributes male students and female students category which forms two groups with the different number of students affected by the different disability causing factors. We assume the null hypothesis that the disabilities of two categories of students are independent of number of students affected by different factors. The calculated Chi-square value is less than the table value at 5 % level of significance. Hence the null hypothesis can be accepted. We can therefore conclude that male and female categories of students in the sample population taken are independent of the disability causing factors in each level.